The two sovereigns : social contradictions of European modernity - Tester, Keith, 1960- (Routledge, 1992)
Keith Tester examines modernity through the prism of the two sovereigns - of the individual and the collectivity. It is a stimulating meditation on the difficult and contradictory experiences of European modernity.